(untitled) (Global Journal of Human-Social Science, 2024)
The average schooling duration of Indian children is 6 7 years It is observed that 47 of students who start in the first standard drop out before completing 10th grade According to the 2019-20 UDISE data more than 8 crore children are not enrolled in any educational institution meaning that one in every four children has never attended school Despite Kerala having the best education system in India based on statistics and studies problems still persist Therefore our study aims to examine the education system in Kerala from the perspective of the most underprivileged community specifically children from tribal groups In India out of the 1652 languages spoken only 47 languages are used as a medium of instruction Additionally there is a growing emphasis on English rather than regional languages The impact of this shift to English as the medium of instruction on the most marginalised sections of society remains a subject of debate